Pembelajaran Ilmu Tajwid Menggunakan Media Wordwall di Rumah Tahfidz Kepenuhan Riau - Romelah Romelah; Sri Mulyani (Reflection : Islamic Education Journal, 2025)
This article discusses the use of engaging and enjoyable learning media, which is essential to support the learning process of students. Moreover, engaging and enjoyable learning media can undoubtedly increase students' motivation to learn. This article explores the utilization of an application, namely Wordwall, as an alternative medium to support the learning process, particularly in teaching Tajweed. In this research, the method used by the researcher is qualitative with a case study approach. Data collection techniques include observation, interviews, and literature review. Data analysis was conducted using descriptive analysis. The results of this study indicate that the use of Wordwall media at Rumah Tahfidz Kepenuhan Riau has proven to be an effective learning tool, especially in teaching Tajweed. This media facilitates teachers in delivering materials in an engaging and interactive way, thereby enhancing students' attention and motivation.